Interactive biking exercise (iBikE) platform to facilitate lower extremity cycling exercise: System design and feasibility - In Cheol Jeong; Finkelstein, Joseph (2012 5th International Conference on Biomedical Engineering and Informatics, 2012)
Lower limb pedalling exercise has been frequently used as a part of comprehensive rehabilitation programs and has been shown to improve functional outcomes in patients with different chronic health conditions. Various pedalling devices are frequently used to facilitate lower extremity training however effective use of these devices at patient homes is hampered by lack of remote connectivity with clinical rehabilitation team, inability to monitor exercise progress in real time using simple graphical representation, and absence of an alert system which would prevent exertion levels exceeding those approved by the clinical rehabilitation team. The goal of this project was to develop an interactive biking exercise (iBikE) platform aimed at addressing these limitations. The platform uses a miniature wireless 3-axis accelerometer mounted on a patient ankle that transmits the cycling acceleration data to a laptop. The laptop screen presents an exercise dashboard to the patient in real time allowing easy graphical visualization of exercise progress and presentation of exercise parameters in relation to prescribed targets. The iBikE platform is programmed to alert the patient when exercise intensity exceeds the levels recommended by the patient care provider. The iBikE platform has been tested in 8 healthy volunteers (age range: 23-55 years) and shown to reliably reflect exercise progress and to generate alerts at pre-setup levels. Implementation of remote connectivity with patient rehabilitation team is warranted for future extension and evaluation efforts.